EFFECT OF APPLICATION METHODS AND RATES OF CALCIUM SOURCES ON SOIL ALUMINUM FORMS - Gabriel, Camila Adaime; Cassol, Paulo Cezar; Campos, Mari Lucia; Mumbach, Gilmar Luiz; Moraes Neto, Mário Chaves (Floresta, 2024)
Effect of application methods and rates of calcium sources on soil aluminum forms. The presence of aluminum (Al) in available forms in the soil can harm cultivated plants. Aluminum forms were evaluated in a Humic Cambisol soil grown with eucalyptus and treated with dolomitic limestone (DL), gypsum (GYP), and lime mud (LM), using surface applications over the total area (TA), to the planting strip (STRIP), and to the planting furrow with incorporation (FRW). The treatments were: Control; DL 3.5 Mg ha-1 TA; DL 1.75 Mg ha-1 STRIP; DL 3.5 Mg ha-1 STRIP; LM 3.5 Mg ha-1 STRIP; DL 3.5 Mg ha-1 + GYP 1.75 Mg ha-1 STRIP; DL 1.75 Mg ha-1 FRW; DL 1.75 Mg ha-1 + GYP 1.38 Mg ha-1 FRW; and GYP 1.38 Mg ha-1 FRW. After 31 and 56 months of applying the treatments, the levels of exchangeable Al (Al3+), Al bound to organic matter (Al - MO) and Al bound to low crystallinity and amorphous oxides (Al - OX) were determined in layers of up to 0.40 m. Al3+ contents decreased in the 0-0.05 m layer when DL and LM were applied in TA and STRIP and, in the lower layers when the first was incorporated in the FRW. Al-OM and Al-OX contents were 2.6 to 5.8-fold higher than Al3+. DL on TA decreases Al3+, Al-OM, and Al-OX contents in the 0-0.05 m layer. GYP application did not affect soil Al contents.